The ancient magus' bride. Volume 12 - Yamazaki, Kore; MacFarlane, Ysabet Reinhardt (Ancient Magus' Bride, 2020)
KEEPING SECRETS. Many different students from different backgrounds attend the fantastical institution of higher learning known as “The College.” They are the nameless, faceless strangers sitting in the next seat, or living in the next dorm room. As Chise begins to come out of her shell and interact with her classmates, she overhears a certain rumor about her roommate, Lucy...